AVALIAÇÃO DO GRAU DE HIDRATAÇÃO AO LONGO DO TEMPO DE ARGAMASSAS ESTABILIZADAS POR PERDA AO FOGO - Mees, Sabrina; Brito, Larissa Aló Pinto; Oliveira, Alexandre Lima de; Calçada, Luciana Maltez; Casali, Juliana Machado (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The mortars were produced with the same ratio of water/ dry materials and the same content of air-entrained admixtures, while three contents of hydration stabilizing admixtures and a mortar without this admixture were evaluated. The ready mix mortars were characterized in the fresh state through the consistency index, specific gravity and air entrained content. In the hardened state, the evaluation of the degree of hydration by ignition loss were evaluated at the ages of 28, 42 and 56 days. The results obtained demonstrate there is no influence of the admixture content of hydration stabilizing on the properties of the mortars in the fresh state. In relation to the degree of hydration of the mortars, there was an increase of the hydrated compounds for the mortars without hydration stabilizing admixtures and the influence of the hydration stabilizing admixtures content. However, for mortars with a hydration stabilizing admixtures, small increment in the degree of hydration was observed in relation to the age of the mortars, in relation to the determined parameters.